Cybervictimization, Self-esteem and Perceived Social Support: Resilience Role as the Mediating Variable - Rini, Amanda Pasca; Salim, Agus (Journal of Educational, Health and Community Psychology, 2025)
Cyberbullying significantly impacts mental health, contributing to decreased self-esteem, self-harm, and suicide among adolescents. While previous research has established links between self-esteem, social support, and cyberbullying, the underlying mechanisms remain unclear, particularly the potential mediating role of resilience. This study aimed to address this gap by examining whether resilience mediates the relationship between perceived social support, self-esteem, and cyberbullying. A quantitative methodology was adopted, involving a sample of 994 middle-school students aged 12 to 17 years from urban regions in East Java, Jakarta, West Java, and Bali. Structural Equation Modeling (SEM) was employed to perform mediation analyses. Findings indicated that resilience does not mediate the relationships among self-esteem, perceived social support, and cyberbullying. Furthermore, self-esteem and perceived social support emerged as stronger direct predictors of cyberbullying in the absence of resilience as a mediator. Although self-esteem significantly predicts resilience, perceived social support exhibited only a limited predictive ability in relation to resilience. These findings highlight the need for further research to explore alternative pathways through which self-esteem and social support influence cyberbullying, as well as the contextual factors that may affect resilience in adolescent populations.